2022
DOI: 10.1002/hbm.26021
|View full text |Cite
|
Sign up to set email alerts
|

Automatic auditory processing features in distinct subtypes of patients at clinical high risk for psychosis: Forecasting remission with mismatch negativity

Abstract: Individuals at clinical high risk (CHR) for psychosis exhibit a compromised mismatch negativity (MMN) response, which indicates dysfunction of pre-attentive deviance processing. Event-related potential and time-frequency (TF) information, in combination with clinical and cognitive profiles, may provide insight into the pathophysiology and psychopathology of the CHR stage and predict the prognosis of CHR individuals.A total of 92 individuals with CHR were recruited and followed up regularly for up to 3 years. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
(72 reference statements)
1
1
0
Order By: Relevance
“…Measures of MMN are correlated to the magnitude of these sensory processing deficits ( 38 ). Consistent with that, recent studies revealed that reduced MMN is particularly present in a subgroup of patients with marked cognitive deficits and poor social functioning ( 34 , 39 , 40 ) and predicts poor response to therapy with common antipsychotics ( 41 , 42 ). Studies on the neurophysiological substrate of MMN reductions have demonstrated associations to hypofunction of the glutamatergic NMDA receptor ( 43 ).…”
Section: Possible Biomarkers For Muscarinic Dysfunction In Schizophreniasupporting
confidence: 63%
“…Measures of MMN are correlated to the magnitude of these sensory processing deficits ( 38 ). Consistent with that, recent studies revealed that reduced MMN is particularly present in a subgroup of patients with marked cognitive deficits and poor social functioning ( 34 , 39 , 40 ) and predicts poor response to therapy with common antipsychotics ( 41 , 42 ). Studies on the neurophysiological substrate of MMN reductions have demonstrated associations to hypofunction of the glutamatergic NMDA receptor ( 43 ).…”
Section: Possible Biomarkers For Muscarinic Dysfunction In Schizophreniasupporting
confidence: 63%
“…ERP components under different paradigms can effectively reflect the abnormal mechanisms of brain function in patients with psychosis. The SHARP team 26 systematically studied the characteristics of mismatch negativity (MMN) in the CHR population. The MMN is a widely studied ERP component that reflects the processing of preattention auditory information.…”
Section: Shanghai At Risk For Psychosis (Sharp)mentioning
confidence: 99%